2020
DOI: 10.1007/s00415-020-10127-8
|View full text |Cite
|
Sign up to set email alerts
|

Nerve ultrasound in hereditary transthyretin amyloidosis: red flags and possible progression biomarkers

Abstract: Background Diagnostic delay of hereditary transthyretin amyloidosis (ATTRv, v for variant) prevents timely treatment and, therefore, concurs to the mortality of the disease. The aim of the present study was to explore with nerve ultrasound (US) possible red flags for early diagnosis in ATTRv patients with carpal tunnel syndrome (CTS) and/or polyneuropathy and in pre-symptomatic carriers. Methods Patients and pre-symptomatic carriers with a TTR gene mutation were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 39 publications
3
27
1
3
Order By: Relevance
“…The CSAs at proximal sites of measurable nerves (median nerves, ulnar nerves and sciatic nerves) were significantly higher than those of healthy controls, compared with distal sites in a same nerve. All this was compatible with the findings of previous studies for nerve ultrasound and magnetic resonance neurography in TTR-FAP patients (7,8,15). Moreover, prominent enlargement of peripheral nerves at proximal sites was not common in most axonal neuropathies (17,18), which could help distinguish TTR-FAP from other axonal neuropathies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The CSAs at proximal sites of measurable nerves (median nerves, ulnar nerves and sciatic nerves) were significantly higher than those of healthy controls, compared with distal sites in a same nerve. All this was compatible with the findings of previous studies for nerve ultrasound and magnetic resonance neurography in TTR-FAP patients (7,8,15). Moreover, prominent enlargement of peripheral nerves at proximal sites was not common in most axonal neuropathies (17,18), which could help distinguish TTR-FAP from other axonal neuropathies.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, prominent enlargement of peripheral nerves at proximal sites was not common in most axonal neuropathies (17,18), which could help distinguish TTR-FAP from other axonal neuropathies. For note, distal enlargement of median nerves was also observed in our study, which might associate with carpal tunnel syndrome in these TTR-FAP patients (8).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Further, this nerve enlargement can also be seen by ultrasound, particularly at entrapment sites ( Figure 2 C,D) [ 54 ]. Podnar et al found that besides common entrapment sites, a pronounced nerve enlargement in a larger cohort of ATTR patients was also seen in proximal segments and plexus [ 55 ], and even of presymptomatic carriers [ 56 ]. This finding suggests ultrasound as an important tool to enable early treatment.…”
Section: Hereditary Transthyretin Related and Sporadic Amyloidosismentioning
confidence: 99%